Spinal Dystonia Associated with Transverse Myelitis in an Adolescent Female: A Case Report - Deginet E; Abebe AM; Abatkun M (Dove Medical Press, 2024)
Endayen Deginet, Abeba Mengesha Abebe, Meskerem Abatkun Department of Pediatrics and Child Health, School of Medicine, College of Health and Medical Sciences, Saint Paul's Hospital Millennium Medical College, Addis Ababa, EthiopiaCorrespondence: Endayen Deginet, Email endayend@gmail.comBackground: Dystonia, one of the most common movement disorders, It was mostly a result of pathology in basal ganglia; there have been increasing numbers of dystonia cases reported in patients with spinal cord pathology.Case Presentation: Here we report, a 14 year old female adolescent from Addis Ababa Ethiopia presented with dystonia of extremities within one month after she was diagnosed with transverse myelitis.Conclusion: Although any spinal cord pathology can result in spinal dystonia, demyelinating diseases are among the leading causes. There are few case reports on dystonic spasm caused by acute transverse myelitis. This case report describes an instance of spinal dystonia associated with transverse myelitis in an adolescent female.Keywords: spinal dystonia, transverse myelitis, adolescent